On the solar activity dependence of midnight equatorial plasma bubbles during June solstice periods - Ajith, K.K.; Tulasiram, S.; Li, GuoZhu; Yamamoto, M.; Hozumi, K.; Yatini, C.Y.; Supnithi, P. (My University, 2021)
The occurrence of midnight Equatorial Plasma Bubbles (EPBs) during the June solstice period of the ascending phase of solarcycle 24, from 2010 to 2014, was studied using data from the 47 MHz Equatorial Atmosphere Radar (EAR) at Kototabang, Indonesia. Theanalysis shows that the occurrence of midnight hour EPBs was at its maximum during the low solar activity year 2010 and monotonicallydecreased thereafter with increasing solar activity. Details of the dependence of midnight hour EPB occurrence on solar activity wereinvestigated using SAMI2 model simulation with a realistic input of E × B drift velocity data obtained from the CINDI-IVM onboard theC/NOFS satellite. Results obtained from term-by-term analysis of the flux tube integrated linear growth rate of RT instability indicate thatthe formation of a high flux tube electron content height gradient (steep vertical gradient) region at higher altitudes, due to the elevatedF layer, is the key factor enhancing the growth rate of RT instability during low solar activity June solstices. Other factors are discussed inlight of the relatively weak westward zonal electric field in the presence of the equatorward neutral wind and north-to-southtransequatorial wind around the midnight hours of low solar activity June solstices. Also discussed are the initial seeding of RT instabilityby MSTIDs and how the threshold height required for EPB development varies with solar activity.
Keywords: Equatorial plasma bubbles; Equatorial ionosphere; Ionospheric instabilities and irregularities